The Role of Indonesian Language in Acquisition of Maritime English Cadets of Shipping Academy - Anggraeny, Elva Febriana; Mudiyanto; Bachtiar, Rahmat Yusuf (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Maritime English has a large enough role in communication on board because no matter how sophisticated and complete the communication tools on board the ship, its function will not be maximized if the user does not have the skills and ability to communicate in accordance with the standards set out in the IMO SMCP which states that the standard language sailor is Maritime English. Based on this, the formulation of the problem in this research is how is the influence of Indonesian as L2 in the acquisition of Maritime English as L3? And how is the production of Maritime English as L3 by L2 Indonesian speakers? This research method is qualitative and quantitative with the type of research that will be used is associative research (relationships) with quantitative analysis methods. Associative research is research that aims to determine the relationship between two or more variables. Based on data processing with SPSS version 26, a correlation value of 0.759 means that there is an influence of Indonesian as L2 in the acquisition of Maritime English as L3. When studying Maritime English L3, cadets are more likely to choose to transfer the language to Indonesian L2 rather than local language L1. However, the accent that is pronounced when speaking Maritime English is still thick with the L3 regional accent.